Transnational research in English language teaching : critical practices and identities - Jain, Rashi; Yazan, Bedrettin; Canagarajah, A. Suresh (Bristol, UK ; Jackson, TN : Multilingual Matters, 2022)
"The edited volume contributes to the comprehensive and inclusive understanding of the global ELT landscape in instructional settings within and across countries. It brings together language teachers, educators and researchers who use their experiences of shuttling across borders to reflect on the shaping of their pedagogical and research practices"--
Frontmatter -- Contents -- Contributors -- 1 A Critical Exploration of the Complex Research Landscape of Transnational Practices and Identities in Global ELT Settings -- Part 1 Transnational Practices and Identities of ELLs in the US -- 2 Understanding Transnational Childhoods through Young Immigrant Children's Photographs -- 3 'I'm not belonged': Examining Transnational Undergraduate Students' Sense of Belonging as English Learners -- 4 Dubious Battle in 'Otherness': Pride or Shame -- 5 Transnational Socialization of a Graduate Student from Turkey: Negotiating Identities, Asserting Agency and Navigating Emotions -- Part 2 Transnational Practitioners and Participants in Global Contexts Beyond the US -- 6 'Started working as a global volunteer ...': Developing Professional Transnational Habitus through Erasmus+ -- 7 Intercultural Experience and Transnational Culture Education: A Case Study of One Novice Teacher's Personal and Professional Development -- 8 National Perspectives on Mexican Transnational EAL Teachers: Ideological and Professional Challenges -- 9 Syrian Immigrants as Transnational TESOL Practitioners in Turkey -- Part 3 Transnational Practices and Identities of TESOL Practitioners in the US -- 10 A Korean-American Teacher's Journey of Professionalization: A TESOL Teacher Educator's Identity Formation across Transnational Contexts -- 11 Two Transnational and Translingual TESOL Practitioners in the United States: Their Capital and Agency -- 12 Teaching as Transnational Spaces: Exploring the Teacher Identity Construction of International Graduate Teaching Associates of Second-Year Writing Courses -- 13 Becoming Critical Transnational English Teachers: A Narrative Inquiry of Fulbright Preservice English Language Teachers -- Afterword -- Index
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: English language -- Study and teaching (Higher) -- Foreign speakers; Transnationalism; Transnationalisme; LANGUAGE ARTS & DISCIPLINES / Study & Teaching; English language -- Study and teaching (Higher) -- Foreign speakers; Transnationalism; Essays; Essays